ChemInform Abstract: Fe(III)/NaBH4‐Mediated Free Radical Hydrofluorination of Unactivated Alkenes. Issue 9 (5th March 2013) - Barker, Timothy; Boger, Dale L.
Abstract The transformation is achieved under exceptionally mild conditions to yield the corresponding Markovnikov addition products.